The effect of ownership type on the performance of commercial banks (Economic studies journal, 2020)
This study aimed know the impact of property type on commercial banks performance and to know the current position of Libyan banking sector in terms of performance efficiency by using suitable financial tools which help to evaluate that, the study also seeks to obtain results and introduce sit of recommendations to support and develop banking reparations. To achieve all that goals the researchers relied on the descriptive method and using quantitative and analytic ways through the financial ratios to evaluate the financial performance of commercial banks which taken as a sample of the study(Sahara bank represents the public sector and Bank of commerce and development represents the private sector) .In order to collect required data the study relied on the financial statements that collected from the study sample to get primary data, as well as the secondary date that obtained from scientific references and official publications. In addition the study found that although the Bank of commerce and development has less market share comparing by Sahara bank but the bank achieved very high financial returns with low risks comparing by Sahara bank and this confirm that the performance of private banks better than the performance of public banks.
Keywords: property type, public banks, private banks, financial ratios, banks performance